FORMING OF CREATIVE CREDO OF ULYANA KRAVCHENKO ON A BACKGROUND SOCIAL AND POLITICAL CHANGES IN GALICHINI OF END ХІХ - BEGINNING OF ХХ AGE - Voloshuк G. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article is made the attempt to characterized the state and formed the creative credo by Ulyana Kravchenko on the shade social-political shifts in Galychyna of the finish ХІХ-begin ХХ century, important place is taken fix participation authoress in women movement in Galychyna besides and in all-Ukrainian at all It is analyzed the national-patriotic and the phemenistic (in channel liberation struggle) motives in her compositions.